2022
DOI: 10.1136/bmjopen-2021-054725
|View full text |Cite
|
Sign up to set email alerts
|

Balance on the Brain: a randomised controlled trial evaluating the effect of a multimodal exercise programme on physical performance, falls, quality of life and cognition for people with mild cognitive impairment—study protocol

Abstract: IntroductionExercise and physical activity have been shown to improve cognition for people living with mild cognitive impairment (MCI). There is strong evidence for the benefits of aerobic exercise and medium evidence for participating in regular strength training for people with MCI. However, people living with MCI fall two times as often as those without cognitive impairment and the evidence is currently unknown as to whether balance training for people with MCI is beneficial, as has been demonstrated for ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The Balance on the Brain randomized controlled trial is currently in progress and is trialling the effectiveness of balance interventions in reducing falls for people with Mild Cognitive Impairment. 79 These type of studies are important. They will assist health professionals in rehabilitation settings to better understand and design preventive and post-fall interventions for people with Mild Cognitive Impairment (with the aim of reducing future falls).…”
Section: Discussionmentioning
confidence: 99%
“…The Balance on the Brain randomized controlled trial is currently in progress and is trialling the effectiveness of balance interventions in reducing falls for people with Mild Cognitive Impairment. 79 These type of studies are important. They will assist health professionals in rehabilitation settings to better understand and design preventive and post-fall interventions for people with Mild Cognitive Impairment (with the aim of reducing future falls).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited as part of the Balance on the Brain randomised controlled trial (RCT) between January 2021 to December 2022. The RCT is recruiting participants across the Perth and Rockingham metropolitan areas of Western Australia (WA) to evaluate the effect of multi-modal exercise on improving balance and reducing falls (Burton et al, 2022). The cross-sectional design included baseline data from all participants in the RCT before the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…The possible physiological and psychological mechanisms by which MCI is associated with falls have been mentioned in several studies. On the one hand, previous study emphasised older adults with MCI showed worse balance capacity (eg, increased anterior–posterior and mediolateral sway) 14 15. Impaired balance capacity indicates difficulty with neurological and musculoskeletal functions that contribute to physical stability 16.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies demonstrated that MCI is significantly associated with falls 9 14. The possible physiological and psychological mechanisms by which MCI is associated with falls have been mentioned in several studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation